2021
DOI: 10.1016/j.heliyon.2021.e06120
|View full text |Cite
|
Sign up to set email alerts
|

First trimester placental mesenchymal stem cells improve cardiac function of rat after myocardial infarction via enhanced neovascularization

Abstract: Acute myocardial infarction (AMI) is the most critical heart disease. Mesenchymal stem cells (MSCs) have been widely used as a therapy for AMI for several years. The human placenta has emerged as a valuable source of transplantable cells of mesenchymal origin that can be used for multiple cytotherapeutic purposes. However, the different abilities of first trimester placental chorion mesenchymal stem cells (FCMSCs) and third trimester placental chorion mesenchymal stem cells (TCMSCs) have not yet been explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It was speculated that the PI3K-Akt signaling pathway was the mainly disturbed pathway involved in the abnormal PVOD-iPSC-EC proliferation and angiogenesis ( Haque and Morris, 2017 ; Wang et al., 2013 ). Therefore, the expressions of downstream genes were detected, and it was found that the components of the PI3K-AKT signaling pathway evidently changed, and that PVOD-iPSC-ECs expressed higher levels of pro-proliferation (PCNA, MCM7, and MCM4) and pro-angiogenesis genes (PDGFD, VEGFA, and TNC), and lower levels of anti-angiogenesis gene ANGPTL1 ( Yu et al., 2021 ) ( Figure 4 C). Phospho-Akt/Total-Akt expression was upregulated in PVOD-iPSC-ECs, when compared with GC-PVOD-iPSC-ECs, indicating activation of the AKT signaling ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…It was speculated that the PI3K-Akt signaling pathway was the mainly disturbed pathway involved in the abnormal PVOD-iPSC-EC proliferation and angiogenesis ( Haque and Morris, 2017 ; Wang et al., 2013 ). Therefore, the expressions of downstream genes were detected, and it was found that the components of the PI3K-AKT signaling pathway evidently changed, and that PVOD-iPSC-ECs expressed higher levels of pro-proliferation (PCNA, MCM7, and MCM4) and pro-angiogenesis genes (PDGFD, VEGFA, and TNC), and lower levels of anti-angiogenesis gene ANGPTL1 ( Yu et al., 2021 ) ( Figure 4 C). Phospho-Akt/Total-Akt expression was upregulated in PVOD-iPSC-ECs, when compared with GC-PVOD-iPSC-ECs, indicating activation of the AKT signaling ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…The study in rats with modeled myocardial infarction showed that transplantation of human placental stem cells improves the contractile function of the left ventricle, significantly reduces scar size, suppresses inflammation and apoptosis, and stimulates angiogenesis [199]. Additional processing of placental cells with hyaluronan ethers of oleic and retinoic acid, besides the pro-angiogenic effect, promotes their expression of cardiac markers connexin 43 and troponin I [179].…”
Section: Placenta-derived Stem Cellsmentioning
confidence: 99%
“…Moreover, fCMSCs exhibit significantly lower expression of antiangiogenic genes (SPRY1 and ANGPTL1) than tCMSCs. Additionally, the improvement in cardiac function achieved by fCMSCs is significantly greater than that achieved by treatment with both tCMSCs and BM-MSCs [ 61 ].…”
Section: Stem Cells In Perinatal Tissuesmentioning
confidence: 99%